Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. Experience of teaching computer courses using Madrasati platform during coronavirus pandemic from the teachers’ perspective Co-Prof. Amal Abdullah Al Ibrahim 2. The reality of using digital stories among students with autism in the early intervention stage from the point of view of female teachers in Jeddah Mrs. Hala Harban Almutiri 3. Learning and Study Strategies according to the Weinstein and Palmer LASSI Model Mr. Mohammed Abdallah Almazruii 4. The Effect of Using Verbal Mathematical Problem Solving on Developing Reading Comprehension among First Grade Middle School Students Mr. Abdulaziz Saeed Yahya Almaadi, Dr. Mousa Abdulmouin Mohammed Alqarni 5. The effect of using the cognitive trips strategy through The Web Quest toward tenth-grade students Motivation in social studies in the Sultanate of Oman Dr. Khalid Nasser Abdullah Al-Toubi, Prof. Mohammed Y. M. Mai 8. The Values Contained in the Developed Books of Islamic Education at the Upper Three Grades in Primary Stage in Saudi Arabia Dr. Fahad Oudah Alatawi 7. The effect of the cognitive apprenticeship strategy on the achievement and memorization of literature and texts among the fifth literary students Dr. Natiq Saeed Ghayyib